2023
DOI: 10.1038/s41598-023-29300-w
|View full text |Cite|
|
Sign up to set email alerts
|

A cross-country study on the impact of governmental responses to the COVID-19 pandemic on perinatal mental health

Abstract: This study aimed to analyse the role of governmental responses to the coronavirus disease 2019 (COVID-19) outbreak, measured by the Containment and Health Index (CHI), on symptoms of anxiety and depression during pregnancy and postpartum, while considering the countries’ Inequality-adjusted Human Development Index (IHDI) and individual factors such as age, gravidity, and exposure to COVID-19. A cross-sectional study using baseline data from the Riseup-PPD-COVID-19 observational prospective international study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…11 The different prevalence rates observed among continents might be attributed to several groups of factors: (a) COVID-19-related variables, like restrictions imposed by governments to limit the contagion, or the impact of COVID-19 infection in terms of mortality and contagion rates; (b) and cultural differences. 51 F I G U R E 5 Forest plot of the pooled prevalence (proportion) of postnatal anxiety.…”
Section: F I G U R Ementioning
confidence: 99%
“…11 The different prevalence rates observed among continents might be attributed to several groups of factors: (a) COVID-19-related variables, like restrictions imposed by governments to limit the contagion, or the impact of COVID-19 infection in terms of mortality and contagion rates; (b) and cultural differences. 51 F I G U R E 5 Forest plot of the pooled prevalence (proportion) of postnatal anxiety.…”
Section: F I G U R Ementioning
confidence: 99%
“…Differences in the provision of care between countries was evident. The best-case scenario estimation of mental healthcare for clinically significant comorbid symptoms of depression and anxiety was 21.6% in Brazil, a country with one of the highest containment and health index (i.e., composite measure based on governmental responses to COVID-19 pandemic indicators, for details see 44 ) among the countries in study 5 and with a high proportion of women reporting that mental healthcare is very important (66%, Supplementary Table 2), a key factor for seeking help. 17 These gaps in mental healthcare may be due to disruptions in antenatal or postnatal mental healthcare during the COVID-19 pandemic, 8 which may have led to either lack of systematic screening and/or referral and/or lack of access to treatment for women screened positive for perinatal mental health problems.…”
Section: Mental Healthcarementioning
confidence: 99%
“…2,4 The estimates of clinically significant symptoms of anxiety (GAD-7 ≥ 10) reaches 30% during pregnancy and 20% in the postpartum in the pre-pandemic vs 36% during pregnancy and 42% in the postpartum in the COVID-19 pandemic in studies conducted in Albania, Brazil, Bulgaria, Chile, Cyprus, Greece, Israel, Malta, Portugal, Spain, Turkey, and the United Kingdom. 2,5 The estimates of recent systematic reviews and of a study conducted in Brazil, Chile, Cyprus, Greece, Israel, Portugal, Spain, Turkey, and the United Kingdom, indicated that clinically significant symptoms of depression and anxiety is around 6.3% during pregnancy and 5.7% postpartum, in the pre-pandemic period vs 15% during pregnancy and 20% in the postpartum in the COVID-19 pandemic. 2,6,7 Despite the high rates of perinatal mental health problems, especially in countries with lower inequality-adjusted human development index 5 during the COVID-19 pandemic, more than 60% of antenatal or postnatal mental healthcare services of 130 countries were disrupted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous outbreaks and pandemics show the deleterious effects of social isolation [13,14], and such isolating behaviors have been intensely stressful for many people. However, evidence is contradictory: at least one study suggests that more stringent government containment measures were associated with better mental health among pregnant women [15], while others find higher COVID-19 restrictions to be associated with more stress and worse mental health [16]. In this study, we examined how various types of social distancing were associated with mental health and stress in a sample of pregnant women.…”
Section: Introductionmentioning
confidence: 97%